PENGEMBANGAN MEDIA PEMBELAJARAN MINI BOOK DIGITAL BERBASIS WEB GOOGLE SITES PADA MATA PELAJARAN IPA BIOLOGI - Aryani Dwi Kesumawardani; Riska Gusti Yani; Nukhbatul Bidayati Haka; Raicha Oktafiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the lack of use of varied, creative and innovative learning media in the classroom so that students often feel bored or have difficulty absorbing learning material. Therefore, researchers are encouraged to develop google web-based digital mini book learning media for junior high school biology science subjects. This study uses research and development (R&D) methods, while the procedures in this study use a 4D development model consisting of define, design, development and disseminate. The product validation stage involves 2 media, material, and language validators. The product trial sample was applied to small groups involving 20 people while the field test involved 60 grade VIII students. The results of the research show that the resulting media product is a mini book digital web-based google sites that have been validated by expert validators obtained an average score of 3,98 (media expert), 3,795 (material expert), and 3,87 (language expert) with the criteria “Valid” and feasible used. In addition, in the small group test the student response questionnaire obtained an average score of 3,815, while in the field test an average score of 3,845 was obtained in the “Very Interesting” category.